The Leadership of Genghis Khan and Its Implications for National Unity - Amri Kusumawardana Sumodiningrat (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The leadership of Genghis Khan has been a topic that continues to captivate the attention of historians and social scientists due to his success in transforming fragmented nomadic tribes across the Central Asian plains into one of the largest and most influential empires in world history. This study aims to examine the leadership values implemented by Genghis Khan in building the Mongol Empire, as well as to understand the implications of these values on the formation and strengthening of national unity. While the Mongol Empire is often remembered for its brutality and widespread conquest wars, history also shows that under Genghis Khan's rule, a period of extraordinary stability emerged, known as Pax Mongolica. This stability brought security along the Silk Road, connecting the East and the West, as well as the North and the South, thus supporting the exchange of goods through trade, the spread of religion and ideologies, and the development of technology and knowledge across civilizations. This research uses a qualitative approach with a historical method, through a literature study of various secondary sources. The analysis is conducted in a descriptive-analytical manner to trace the dynamics of power, military strategy, and the social-political values that formed the foundation of Genghis Khan's leadership. The findings show that Genghis Khan’s success was not solely driven by military power, but also by the application of visionary and adaptive leadership principles. He implemented a meritocratic system in the appointment of officials and military commanders, enforced laws through the Yasa, which functioned as the empire’s constitution, and established an inclusive governance structure that involved various ethnicities and religions in the administration. These values created social stability, strengthened the legitimacy of power, and fostered loyalty that transcended tribal and racial boundaries. The findings affirm that Genghis Khan’s leadership had a strong implication for the formation of national unity because he placed justice, competence, and legal order as the main pillars of governance. In a contemporary context, these values are relevant as inspiration for building a multicultural and democratic nation, where social justice, openness, and meritocracy serve as the foundation for creating sustainable national cohesion.